Coordinated operation schedule of microgrids in consideration of penetration of variable renewable energy sources - Hirotaka Takano; Ryota Goto; Thin Zar Soe; Hiroshi Asano (Energy Reports, 2020)
Operation schedule for microgrids has an important role to manage the electric power supply and demand efficiently. This paper presents a problem formulation and its solution method to obtain a coordinated operation schedule of controllable components in the microgrids. In the problem formulation, uncertainty originated from variable renewable energy sources is introduced. By utilizing characteristics of the formulated problem, dimension of its solution space is reduced, and thus a combined solution method of binary particle swarm optimization and quadratic programming is applicable in the proposed solution method. Validity of the authors' proposal is verified through discussions on numerical results.
Keywords: 330; Binary particle swarm optimization (BPSO); Microgrids; Quadratic programming (QP); Supply-demand management; Uncertainty